Profile of osteophyte location in different grades of functional status in patients with knee osteoarthritis - Mesanti, O; SETIYOHADI, BAMBANG; Kasjmir, Yoga I; Budihusodo, U; Oemardi, M (Indonesian Journal of Rheumatology, 2010)
Background. Osteophyte is a reparative response to cartilage breakdown in osteoarthritis (OA) and osteophyte formation is a knee stabilizing factor. Disability could be found in patients with knee OA. Objective. To identify the profile of osteophyte formation (location, size, and direction) based on knee radiograph and functional status examination in knee OA patients who presented to the Rheumatology Clinic, Cipto Mangunkusumo Central National General Hospital.Methods. Samples were taken by consecutive approach. Knee radiographs (weight bearing anteroposterior and30 degrees flexion skyline views) and functional status examinations were performed on 100 patients with knee OA (90 females and 10 males with ages ranging from 51 to 74 years old). A radiologist assessed films for osteophyte profile such as location, size, and direction according to standard atlas. One knee with the severe radiological assessment based on OA grade was selected from one patient to be the profile. LequesneAlgofunctional Index was also taken from the patients. Results. The site of osteophyte in patients with knee OA was mostly found at lateral femur (85/100 subjects). Based on specific location, grade 2 osteophyte at lateral femur was the most frequent size (49/100 subjects) and osteophyte extending toward the lower middle atlateral patella (65/100 subjects) was the most frequent direction of osteophyte. The most frequent profile for size and direction of osteophyte at specific location was the grade 2 osteophyte extending toward the lower middle at lateral patella (35/100 subjects). Severe functional status impairment was found in 53% of the patients. The most frequent functional status found according to specific location of osteophyte was severe functionalstatus impairment in patients with oste ophyte at lateral femur (46/100 subjects). The most frequent functional status of OA patients based on the size and direction of osteophyte at specific location was the severe functional impairment in the patients with grade 2 osteophyte at lateral femur (27/100 subjects) and the patients with osteophyte extending towards the lower middle at lateral patella (37/100 subjects) respectively.Conclusions. Osteophyte at lateral femur, osteophyte at lateral tibiofemoral compartment, grade 2 osteophyte at lateral femur, and osteophyte extending toward the lower middle at lateral patella were the profiles of osteophyte which mostly showed severe functional status impairment in patients with knee OA.